A Novel Approach for Differential Privacy-Preserving Federated Learning - Anis Elgabli; Wessam Mesbah (IEEE Open Journal of the Communications Society)
In this paper, we start with a comprehensive evaluation of the effect of adding differential privacy (DP) to federated learning (FL) approaches, focusing on methodologies employing global (stochastic) gradient descent (SGD/GD), and local SGD/GD techniques. These global and local techniques are commonly referred to as FedSGD/FedGD and FedAvg, respectively. Our analysis reveals that, as far as only one local iteration is performed by each client before transmitting to the parameter server (PS) for FedGD, both FedGD and FedAvg achieve the same accuracy/loss for the same privacy guarantees, despite requiring different perturbation noise power. Furthermore, we propose a novel DP mechanism, which is shown to ensure privacy without compromising performance. In particular, we propose the sharing of a random seed (or a specified sequence of random seeds) among collaborative clients, where each client uses this seed to introduces perturbations to its updates prior to transmission to the PS. Importantly, due to the random seed sharing, clients possess the capability to negate the noise effects and recover their original global model. This mechanism preserves privacy both at a “curious” PS or at external eavesdroppers without compromising the performance of the final model at each client, thus mitigating the risk of inversion attacks aimed at retrieving (partially or fully) the clients’ data. Furthermore, the importance and effect of clipping in the practical implementation of DP mechanisms, in order to upper bound the perturbation noise, is discussed. Moreover, owing to the ability to cancel noise at individual clients, our proposed approach enables the introduction of arbitrarily high perturbation levels, and hence, clipping can be totally avoided, resulting in the same performance of noise-free standard FL approaches.